The Influence of Green Knowledge and Green Perceived Value on Purchase Intention Mediated by Green Lifestyle - Yulianingsih, Yulianingsih; Laela, Laela; Sardju, Himawan (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the influence of green knowledge and green perceived value on purchase intention mediated by green lifestyle on Gen Z tumbler product users in Indonesia. This study was conducted through a quantitative approach with a total sample of 200. The sampling technique used was non-probability sampling with a purposive sampling approach. Data were processed using Structural Equation Modeling with the Smart Partial Least Square statistical program. The results of this study prove that: Green knowledge has no effect on purchase intention; Green knowledge has a positive effect on green lifestyle; Green perceived value has a positive effect on purchase intention; Green perceived value has a positive effect on green lifestyle; Green lifestyle has a positive effect on purchase intention; Green knowledge has a positive effect on purchase intention through green lifestyle as a mediating variable; and green perceived value has a positive effect on purchase intention through green lifestyle as a mediating variable.